Relating the visceral factor of pain to domain-specific risk attitudes - Adriana N. König; Birgit Linkohr; Annette Peters; Karl-Heinz Ladwig; Michael Laxy; Lars Schwettmann (Journal of Behavioral Decision Making, 2023)
Visceral factors are negative emotions and drive and feeling states that grab people's attention and motivate them to engage in certain behaviors. They can contribute to discrepancies between an individual's long-term self-interest and their actual behavior. One such discrepancy concerns risk-taking in health contexts as well as in a variety of other domains such as financial or career-related decisions. This study examines the relationship between somatic symptoms of pain and domain-specific risk attitudes in participants of a large population-based cohort study. Somatic symptoms refer to back pain; pain in arms, legs, or joints; and headache. We show that the association between pain and risk attitudes is especially robust for the financial and leisure/sports domain across different model specifications. Pain is negatively associated with willingness to take risks in both domains. When controlling for fatigue (another visceral factor), the relationship between pain and risk attitudes persists only in the financial context. However, associations between fatigue and risk attitudes emerge in the general, health, leisure/sports, and career domains. We discuss potential implications of our findings especially in light of financial decision-making.
Keywords: 650; domain-specific willingness to take risks; pain; risk attitudes; visceral factors